Bonding for 3D ICs and heterogeneous system - Chia, Hong Ling. (2009)
In the current two-dimensional (2D) integrated circuits, the chip size is increasing despite the reduction in feature size. This leads to increased complexity of chip design as more and more transistors are closely packed. Hence, three-dimensional technology is the solution. In general, 3D technology is any technology that stacks semiconductor devices on top of each other and uses vertical, instead of peripheral, interconnects between the wafers. In this report, thermocompression bonding would be used to bond the materials (copper to copper and gold to gold) together for interconnect and packaging applications. Due to surface roughness, initial contacts will be formed between surface asperities under thermocompression bonding. With increase loads and temperatures applied, the microscopic contacts between the two copper to copper regions or gold to gold regions start to deform, which increase the contact area, and finally diffuse into each other to form a bond. Optimization of the surface cleanliness, pressure, temperature and bonding duration could lead to a high quality bond. It was found that a temperature of 4000C and applied load of 2400 g led to stronger bonds for both copper-copper bonding and gold-gold bonding as compared to a temperature of 2000C and applied load of 400 g.